2014
DOI: 10.1007/s11064-014-1349-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factors, Clinical Features and Gender Differences in Depression

Abstract: Recent studies have evaluated the role of brain-derived neurotrophic factor (BDNF) in mood disorders; however, little is known about alterations in nerve growth factor (NGF) and glial cell line-derived neurotrophic factor (GDNF). The aim of this study was to evaluate differences among serum neurotrophic factors (BDNF, NGF and GDNF) in depressed patients and healthy controls and to verify the association between serum neurotrophic levels and clinical characteristics in a young, depressed population stratified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 43 publications
7
56
3
Order By: Relevance
“…In regard to trait depression, Lang et al [59] as well as Terracciano et al [60] found that mentally healthy subjects with depressive personality traits have lower serum BDNF concentrations than subjects without these personality traits. Moreover, female patients were over-represented in our sample (61.8%), which might account for our finding that disease duration is associated with decreased BDNF levels as shown before by de Azevedo Cardoso et al [61]. …”
Section: Discussionsupporting
confidence: 52%
“…In regard to trait depression, Lang et al [59] as well as Terracciano et al [60] found that mentally healthy subjects with depressive personality traits have lower serum BDNF concentrations than subjects without these personality traits. Moreover, female patients were over-represented in our sample (61.8%), which might account for our finding that disease duration is associated with decreased BDNF levels as shown before by de Azevedo Cardoso et al [61]. …”
Section: Discussionsupporting
confidence: 52%
“…However, BDNF was downregulated in depressed patients. Accordingly, a BDNF decrease has already been reported in depressed patients [45] and a recent meta-analysis showed that altered peripheral BDNF levels are associated with ongoing depressive disorders [46]. Clearly this implies that mood dysfunction in ALS is not only a mere adaptive phenomenon to a progressive overwhelming disability, but a complex phenotypic trait regulated by specific biological mechanisms that might be amenable to early dedicated interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has pointed to a dysregulation of neurotrophic processes in relation to depressive disorders [10,11,[29][30][31][32]. A recent meta-analysis indicated that the Met allele of the BDNF Val66Met polymorphism moderated the relationship between stressful life events and the development of depression [33].…”
Section: Discussionmentioning
confidence: 99%